2018
DOI: 10.4103/jhrs.jhrs_72_18
|View full text |Cite
|
Sign up to set email alerts
|

Consensus statement on the use of oral contraceptive pills in polycystic ovarian syndrome women in India

Abstract: Objective:To provide consensus recommendations for health-care providers on the use of oral contraceptive pills (OCPs) in polycystic ovarian syndrome (PCOS) women in India.Participants:Extensive deliberations, discussions, and brainstorming were done with different fraternities (specialists) being involved. These included endocrinologists, gynecologists, reproductive endocrinologists, dermatologists, public health experts, researchers, and a project manager with a team to develop the guideline.Evidence:Publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 220 publications
0
11
0
Order By: Relevance
“…It was revealed in the regression analysis that participants who used contraceptives were 4 times more likely to have PCOS. It is worthwhile mentioning that contraceptives are also used to treat hirsutism [ 34 , 35 ], apart from their use in treatment of PCOS [ 35 ]. This finding may have resulted either due to treatment of hirsutism since three quarter of our sample had some level of hirsutism and/or, as a treatment of PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…It was revealed in the regression analysis that participants who used contraceptives were 4 times more likely to have PCOS. It is worthwhile mentioning that contraceptives are also used to treat hirsutism [ 34 , 35 ], apart from their use in treatment of PCOS [ 35 ]. This finding may have resulted either due to treatment of hirsutism since three quarter of our sample had some level of hirsutism and/or, as a treatment of PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…Progestogen suppresses LH secretion and restrains androgen production by ovarian and adrenal glands. It also competes with androgen receptor and prevents subsequent androgen actions ( 89 , 100 ). After 6 months of OCP treatment, testosterone, glucose, and LH levels were reduced, and hirsutism improvements were seen.…”
Section: Pharmacogenomics In Pcosmentioning
confidence: 99%
“…Overall, these data indicated that patients with PCOS could be linked to the future development of cardiovascular disease (CVD) and venous thromboembolism [5][6][7][8]. Combined oral contraceptives (COCs) have been considered the rst-line therapy for PCOS women with menstrual irregularity and clinical and/or biochemical hyperandrogenism who do not wish to become pregnant [9][10][11]. However, some deleterious metabolic and in ammatory effects have been demonstrated with the association between PCOS and COC use [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%